Entrepreneurial Ecosystems – A Review - Karthik, Neeradi; Anjaneyulu, Ch. (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The entrepreneurial ecosystem has emerged as a topic of research and debate among researchers and policy makers. Entrepreneurial ecosystems have captured the attention of nations in transforming their economies around the creation of innovative products and services, leading to wealth creation and international competitiveness. The literature on entrepreneurial ecosystems is fragmented, yet no study has paid attention to integrating the available studies. This paper aims to provide an overview of the entrepreneurial ecosystem literature in order to create the following papers. First, this article provides an overview of entrepreneurial ecosystem studies. This study is therefore a systematic effort to map the research gaps and gaps on the topic of Entrepreneurial Ecosystem. Second, by identifying knowledge gaps in the current literature, we suggest an avenue for future entrepreneurial ecosystem research. This study supports policy makers and researchers in developing new policies leading to regional systems of innovation and entrepreneurship.